2022
DOI: 10.3390/ijms23084451
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 Expression and Apoptosis Initiation in Crayfish and Rat Peripheral Neurons and Glial Cells after Axonal Injury

Abstract: Neurotrauma is among the main causes of human disability and mortality. The transcription factor E2F1 is one of the key proteins that determine the fate of cells. The involvement of E2F1 in the regulation of survival and death of peripheral nerve cells after axotomy has not been previously studied. We, for the first time, studied axotomy-induced changes in the expression and localization of E2F1 following axonal injury in rats and crayfish. Immunoblotting and immunofluorescence microscopy were used for the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Since axotomy does not cause DNA damage, potential signals for p53 synthesis include transcription factors such as E2F1, c-Myc, p38, as well as the universal second messenger H 2 S. An increase in the level of these proteins was found in axotomized VNC ganglia [52]. In a recent study, we found an increase in the expression of E2F1 in MRN, VNC of crayfish, as well as ganglia of the dorsal roots of the spinal cord during axotomy [53]. It has been shown that H 2 S can regulate the expression of E2F1 [54].…”
Section: Discussionmentioning
confidence: 72%
“…Since axotomy does not cause DNA damage, potential signals for p53 synthesis include transcription factors such as E2F1, c-Myc, p38, as well as the universal second messenger H 2 S. An increase in the level of these proteins was found in axotomized VNC ganglia [52]. In a recent study, we found an increase in the expression of E2F1 in MRN, VNC of crayfish, as well as ganglia of the dorsal roots of the spinal cord during axotomy [53]. It has been shown that H 2 S can regulate the expression of E2F1 [54].…”
Section: Discussionmentioning
confidence: 72%
“…The radiation-induced neuropathy of the sciatic nerve has reported the presence of tissue apoptosis and confirmed dysregulation of Bcl-2 and Bax expression in sciatic nerve tissue [ 173 , 174 , 175 ]. In addition, the cisplatin-resistant ovarian cancer cell line model also exhibited apoptosis via intrinsic and extrinsic mechanisms incorporating p53 alterations [ 176 ].…”
Section: Resultsmentioning
confidence: 96%